Analysis of Corner Kick Success in Laliga Santander 2019/2020 - Michalis Mitrotasios; Claudio Casal; Vasilis Armatas; Jose Losada; Ruben Maneiro (Asociación Española de Ciencias del Deporte, 2021)
Abstract: It is well documented that set pieces represent 30% to 40% of goals scored in elite football, however most studies on set pieces have focused on the analysis of special competitions (World Cup, Euro etc). Thus the purpose of this study was to examine the effectiveness of corner kick strategies used in LaLiga Santander during the 2019/2020 season, to identify the Key Performance Indicators (KPI) associated with the outcome of corners kicks and to develop a successful execution model. In total, 3,620 corner kicks executed in 380 matches were examined through univariate (analysis of proportions), bivariate (Chi-square test for independence χ² and ROC area) and multivariate analysis (logistic regression). Results showed that 105 goals (2.9%) were scored from corner kicks. The following KPI were associated with outcome of corner kicks: final result (χ² = 10.644, p = 0.002), time (χ² = 10.422, p < 0.005), number of intervening attackers (χ² = 24.863, p < 0.001), final attempt zone (χ² = 203.13, p < 0.001), number of passes and second play (χ² = 26.071, p < 0.001). The most effective execution model consisted of a direct delivery, shooting to goal from the front zone or second post. The results present here enhance coaches understanding on factors that affect corner kicks performance and the most efficient mode of execution.